Factors associated with the size of the adhesio interthalamica based on 3.0-T magnetic resonance images. (January 2019) - Yasaka, Koichiro; Akai, Hiroyuki; Kunimatsu, Akira; Kiryu, Shigeru; Abe, Osamu
Background: Adhesio interthalamica (AI) is a small structure connecting bilateral thalami. Purpose: To evaluate the effects of patient age, sex, and lateral diameter of the third ventricle on the long diameter of the AI using multivariate analyses based on magnetic resonance (MR) images obtained with 3.0-T scanners. Material and Methods: This clinical retrospective study included images of 153 patients who underwent MR examination using 3.0-T scanners. The long diameter of the AI and lateral diameter of the third ventricle were measured on images in the mid-sagittal plane and axial plane at the anterior commissure, respectively. Univariate and multivariate analyses were performed. Results: AI was observed in 138 patients (70 men, 68 women; mean age = 63.7 ± 13.7 years; mean AI size =5.34 ± 1.63 mm). By univariate analyses, patient age (r = −0.262, P = 0.002), sex ( P = 0.010), and lateral diameter of the third ventricle (r = −0.642, P < 0.001) were significantly associated with the long diameter of the AI. With multiple linear regression analyses with a stepwise selection of parameters, only the lateral diameter of the third ventricle (estimate = −0.432, P < 0.001) was significantly associated with the long diameter of the AI. The lateral diameter of the third ventricle was longer in patients without AI (15 patients) than in those with AI ( P = 0.006). Conclusion: The lateral diameter of the third ventricle was a major factor negatively associated with the long diameter of the AI.